Maintaining the blind in sham controlled interventional trials: lessons from the EPISOD study - Cotton, Peter; Pauls, Qi; Wood, April; Durkalski-Mauldin, Valerie (Endoscopy International Open, 2019)
Objective and study aims This study was designed to demonstrate the techniques used and the effectiveness of blinding in the EPISOD study (Evaluating Predictors and Interventions in Sphincter of Oddi Dysfunction). This was a large sham-controlled trial evaluating the efficacy of endoscopic sphincterotomy treatment for patients with suspected sphincter of Oddi dysfunction. Patients and methods We describe the methods intended to ensure that the subjects, caregivers and those assessing the outcomes were blinded to the treatment allocation and systematically assess the success of subject blinding procedures using the Bang’s Blinding Index (BI) for each treatment arm as an indicator of potential unblinding.Results Blinding procedures proved to be acceptable and adhered to by the study team at each site. The BI indicated “wishful thinking” by the subjects regardless of treatment assignment, even when they were confident in their opinions. Conclusion We conclude that it is possible to design and maintain a system for blinding the treatment allocation in a sham-controlled interventional study. Treatment guess plus confidence in the guess should be collected to examine the success of blinding procedures. The EPISOD study provides a blueprint for future sham-controlled trials in endoscopy.